Three dimensional heteroatom-doped carbon composite film for flexible solid-state supercapacitors. Issue 6 (8th January 2016) - Zou, Ben-Xue; Gao, You; Liu, Bo; Yu, Yongpeng; Lu, Yanhua
Abstract : Three dimensional (3D) heteroatom-doped active carbon as a flexible supercapacitor electrode is explored with a starting material of silkworm fibers and low molecular weight phenol resin composite. Abstract : Three dimensional (3D) heteroatom-doped active carbon as a flexible supercapacitor electrode is explored with a starting material of silkworm fibers and low molecular weight phenol resin composite. The silk fiber offers a 3D interconnected network and high content of oxygen and nitrogen functionalities, leading to a unique hierarchical structure and a high performance of the electrode. The combination of phenolic resin with silk fibers increases mechanical robustness and specific capacitance of the composite. The porous carbon composite electrode shows a high gravimetric specific capacitance of 239 F g −1 and areal specific capacitance of 637 mF cm −2 at a current density of 0.57 A g −1 . The flexible solid-state supercapacitor assembled with two electrodes in Na2 SO4 /PVA gel electrolyte exhibits an energy density of 17.2 W h kg −1 at a power density of 207 W kg −1 . The capacitance retention of 116% after 10 000 charge–discharge cycles over a voltage range of 1.6 V illustrates the excellent cyclic stability of the supercapacitors and indicates great potential applications for energy storage devices.